The short-term effects of mulching on thesoil-dwelling arthropod community after a wildfire - Silva, Tiago van der Worp da (2018)
Forest fires are common events in the Mediterranean basin, but due to human action and climate change, these have been increasing, especially in Portugal. It is in this context that a larger number of studies have emerged in regard to the impacts of forest fires on ecosystems, with special focus on the effects on soil and mitigation strategies in the post-fire period. In this regard, the application of mulch is one of the mitigation strategies studied since it is considered inexpensive and effective in reducing erosion and loss of soil nutrients in the post-fire. Moreover, the impacts of organic coverages application on soil fauna are still poorly understood. This study aims to assess the effect of the application of various mulch densities in the soil on the invertebrate community in a eucalyptus plantation, immediately after the fire. The ground fauna covered in this study were soil arthropods, a large existing community regarded as reliable bioindicators. The type of mulch used was chopped eucalyptus bark. The study area, located in North-Central region of Portugal, is characterized by eucalyptus plantations in a schist soil. This study was conducted in order to understand the extent of the effects that mulch could produce in a short period after a fire. In order to achieve adequate results, different areas with and without the application of mulch, at different densities were selected and monitored for 5 months after the fire. Sampling was carried out with pitfall traps and identification of the collected specimens was made at Order level. The results suggest differences between the monitoring months and absence of differences among the densities of mulch application, suggesting seasonality as influence factor on the total community abundance. Small differences in the community richness suggested that a low density of mulch provided a faster ecological succession. The application of mulch also raised the hypothesis that it may have introduced unwanted specimens into the ecosystem.